2018
DOI: 10.1007/978-3-319-63682-5
|View full text |Cite
|
Sign up to set email alerts
|

Internet Election Campaigns in the United States, Japan, South Korea, and Taiwan

Abstract: translation, reprinting, reuse of illustrations, recitation, broadcasting, reproduction on microfilms or in any other physical way, and transmission or information storage and retrieval, electronic adaptation, computer software, or by similar or dissimilar methodology now known or hereafter developed. The use of general descriptive names, registered names, trademarks, service marks, etc. in this publication does not imply, even in the absence of a specific statement, that such names are exempt from the relevan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…While changes have occurred since 2013, it is difficult to say that digital campaigning has transformed Japanese elections. Some studies have found that Japanese citizens who actively engage with digital campaigns are more likely to turn out to vote, report greater political efficacy and have more positive feelings towards politicians (Kiyohara, Maeshima and Owen 2018;Kobayashi and Ichifuji 2015). However, the challenge is that many politicians and voters, especially those who are older, are still hesitant to engage in politics online.…”
Section: Implications Of Digital Campaigning For Political Finance An...mentioning
confidence: 99%
See 2 more Smart Citations
“…While changes have occurred since 2013, it is difficult to say that digital campaigning has transformed Japanese elections. Some studies have found that Japanese citizens who actively engage with digital campaigns are more likely to turn out to vote, report greater political efficacy and have more positive feelings towards politicians (Kiyohara, Maeshima and Owen 2018;Kobayashi and Ichifuji 2015). However, the challenge is that many politicians and voters, especially those who are older, are still hesitant to engage in politics online.…”
Section: Implications Of Digital Campaigning For Political Finance An...mentioning
confidence: 99%
“…While there are certainly examples of politicians who are active online, such as the previously mentioned Kono, many continue to prefer traditional styles of campaigning and worry that expanding their Internet activities will only open them up to greater harassment (Wilson 2014). Japanese voters also have a relatively high level of trust in traditional media and news organizations but are relatively less likely to interact with news on social media, which makes it difficult for politicians to mobilize voters online (Kiyohara, Maeshima and Owen 2018).…”
Section: Implications Of Digital Campaigning For Political Finance An...mentioning
confidence: 99%
See 1 more Smart Citation